The Influence of Religiosity and Destination Image on Tourist Decisions From The Perspective of Religious Moderation (A Study of Tourists at Puja Mandala Bali) - Siska Yuli Anita; Esti Liana (Greenation Research & Yayasan Global Resarch National, 2026)
The aim of this research is to determine the partial and simultaneous influence of religiosity and destination image on tourist decisions. This type of research is quantitative research with a sampling technique, namely the Accident Sampling method (determining the sample by chance). The exact population in this study is not known (Unknown Population) so that in taking samples using the formula according to Sujarweni, the sample in this study was 96 respondents and the sample selection criteria was that they were Mandala puja visitors, aged 25-50 years. By using a data processing tool in the form of the SPPS vers 20 application. The results of the research that has been carried out show that simultaneously religiosity and destination image have an influence on tourists' decisions, while partially religiosity has no effect on tourists' decisions and destination image has an influence on tourists' decisions.